INVESTİGATİNG THE QUALİTY OF LİFE AND İTS İNFLUENCİNG FACTORS AMONG THE FACULTY MEMBERS OF PUBLİC UNİVERSİTİES İN IRAN AND TURKEY (CASE STUDY OF VAN YUZUNCU YİL AND URMIA UNİVERSİTY) - ESMAEILI, Narmin; DULEK, Bulut (International Journal of Business Management and Entrepreneurship, 2023)
The WHO defines quality of life as an individual's perception of their position in relation to their goals, expectations, and concerns, influenced by various factors such as physical health, psychological state, independence, social relationships, personal beliefs, and environment. It encompasses the comfort and satisfaction of people's living conditions. Most research on quality of life focuses on medicine, psychology, and social sciences. The purpose of this research is to investigate the quality of life of the academic staff of the university. In this research, it has been tried to measure the perception of the quality of life with the application made in Urmia and Van Yuzuncu Yil universities. The main question of the research is to investigate the impact of demographic factors on the quality of life of academic staff members of public universities in Iran and Turkey. This research was done with a descriptive-analytical method and a survey method. The quality of life scale of the World Health Organization was used as a data collection method. The statistical population of this research is all the academic staff members of Van Yuzuncu Yil and Urmia universities. Its sampling is 335 people from the scientific staff of public universities of two countries, Iran and Turkey, which was obtained by stratified random sampling, which is of proportional allocation type based on Cochran's formula. As a result of the analysis conducted to investigate the difference between demographic variables (gender, age, marital status and educational title), no difference was observed in the perception of the quality of life of academics working in Urmia and Van Yuzuncu Yil Universities. Also, the examination of the physical health status of the participants showed that the average physical health status of Urmia University faculty members is higher. Similarly, in the examination of the social health status, the average scores of the faculty members of Urmia University were higher than the average scores of the faculty members of Van Yuzuncu Yil University. This study was completed by writing the conclusion section and presenting various suggestions.